Circadian entrainment by light and host in the Chagas disease vector, Triatoma infestans - Valentinuzzi, Verónica Sandra (2013)
Triatoma infestans (Reduviidae: Triatominae, "kissing bug") is the main insect vector of Trypanosoma cruzi, the causative agent of Chagas disease, a chronic trypanosomiasis infecting 10 million people world-wide. This hematophagous bug feeds on diurnal and nocturnal species during each host's quiescent time. As the hosts are also its major predators, kissing bugs are subjected to dual selective pressures from a single source. Therefore, synchronization of feeding with the host's behavior is critical to the insects' survival. We show that nonphotic signals linked to the host eclipse the role of light and dark as the primary circadian zeitgeber for these bugs, although light still strongly inhibits locomotor behavior directly. In nature, this combination provides the insect with great flexibility in organizing physiology and behavior: anticipating a quiescent host or avoiding its potential predation while remaining directly responsive to immediate environmental conditions. Manipulation of nonphotic entrainment could be a useful chronobiotic tool in the control of Chagas disease.